Launch of the women’s political participation training curriculum: Sharing a curriculum co-developed with ActionAid Nigeria and its impacts on rural women in southwest Nigeria - Adida, Claire; Kosec, Katrina; Kyle, Jordan; Mo, Cecilia Hyungjung; Arriola, Leonardo; Matanock, Aila; Adeyanju, Dolapo; Fisher, Rachel (International Food Policy Research Institute, 2024)
Study motivation • Government policies affect everyone, yet women are underrepresented in policymaking globally (Duflo 2012; Lawless 2015) and in Nigeria specifically (Ragasa et al. 2023) • Women’s participation in politics and civic life remains low, but helps support women’s livelihoods (Iversen and Rosenbluth 2006)